The Reception of Anna Akhmatova’s Creativity in the Literature of the Lithuanian Exodus (Henrikas Radauskas, Alfonsas Nyka-Niliūnas, Tomas Venclova) - Ivinskaja, Aliona Sofija Sofija (Literatūra, 2018)
[full article and abstract in Lithuanian; abstracts in English and Russian]This article discusses the memoirs, diaries, translations, dedications, poetry and critical works of three Lithuanian exodus poets: Henrikas Radauskas, Alfonsas Nyka-Niliūnas and Tomas Venclova. These Lithuanian poets of the exodus are hardly possible to associate with any kinds of literature movements. Therefore, the reception of Akhmatova’s creative work will be reviewed separately in the context of the creative heritage of the selected authors. Under the new concept of reception, the perception process is not a constant fact – it is a changing, dynamic phenomenon. The theory of reception considers the most important aspect – the accepting side – therefore, it is important to analyze the horizons of the expectations of these Lithuanian poets, their aesthetic perception of art and the way they evaluate poetry. This article takes into account the “horizon of expectation” of the Lithuanian poets, their aesthetic attitudes, perception of art in general and poetry in particular, as well as some features of their poetic creativity.Рецепция творчества Анны Ахматовой в литературе литовского зарубежья (Генрикас Радаускас, Альфонсас Ника-Нилюнас, Томас Венцлова)В статье рассмотрены воспоминания, дневники, переводы, дедикации, поэтические тексты трех поэтов литовского зарубежья – Генриха Радаускаса, Альфонсаса Ника-Нилюнаса и Томаса Венцловы. Этих представителей литературы вряд ли можно отнести к какому-либо одному литературному течению, поэтому их рецепция творчества Ахматовой рассматривается в контексте творчества каждого из названных поэтов в отдельности. В свете современной теории рецепции процесс восприятия не является фактом, данным раз и навсегда, это динамический процесс, в котором центральное место занимает принимающая сторона. В статье учитывается «горизонт ожидания» литовских поэтов, их эстетические установки, восприятие искусства вообще и поэзии в частности, а также некоторые особенности их поэтического творчества.
Keywords: Akhmatova, reception, Venclova, Radauskas, Nyka-Niliūnas, exodus, Lithuanian literature